Hybrid gold nanoparticles as well as preparation method and application thereof

By using the complexation reaction of the star-shaped polymer template and chloroauric acid, water-soluble gold nanoparticles are prepared, which solves the problems of easy agglomeration and poor stability of existing gold nanoparticles, and achieves efficient miRNA detection.

CN119681258AActive Publication Date: 2025-03-25TAN KAH KEE INNOVATION LAB +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411822650.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-25
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing gold nanoparticles are prone to agglomeration during the preparation process, have poor stability, are difficult to store for a long time, and have low yields, cannot be used in high concentrations, and have a single post-modification method, which limits the efficient detection of miRNAs.

Method used

The star-shaped polymer template was used to complex with chloroaulic acid, and water-soluble gold nanoparticles with controllable size, uniform morphology and good stability were prepared under the action of a reducing agent. The method includes the preparation of the polymer PAMAM-PBLG-PEG and complexation reaction with chloroauric acid, through click reaction and deprotection steps to obtain hybrid gold nanoparticles suitable for miRNA detection.

Benefits of technology

The gold nanoparticles are controlled in size, uniform morphology and improved stability, solved the problems of agglomeration and stability, improved the productivity and concentration usage ability, and provided effective detection reagents for efficient detection of miRNA.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119681258A_ABST
    Figure CN119681258A_ABST
Patent Text Reader

Abstract

The invention provides hybrid gold nanoparticles as well as a preparation method and application thereof, and relates to the technical field of novel biomedical materials. The hybrid gold nanoparticles comprise a star-shaped polymer template and gold nanoparticles which are loaded on the star-shaped polymer template (PAMAM-PLG-PEG). According to the preparation method, a star-shaped polymer template (PAMAM-PLG-PEG) is complexed with a precursor chloroauric acid, and under the action of a reducing agent, the water-soluble hybrid gold nanoparticles which are controllable in size, uniform in morphology and good in stability are obtained; and the hybridized gold nanoparticles can be applied to the detection of miRNA (micro Ribonucleic Acid).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new biomedical materials, and in particular to hybrid gold nanoparticles and a preparation method and application thereof. Background Art

[0002] Tumors are malignant diseases with high morbidity and mortality, posing a huge threat to human health. Early diagnosis is conducive to early intervention and treatment of tumors, reducing morbidity and mortality, increasing survival rates, and improving the quality of life of patients. Liquid biopsy refers to an in vitro diagnostic technology that uses human body fluids as a source of specimens for detection and analysis. Due to its low invasiveness, liquid biopsy technology is considered to be the first choice for early diagnosis of tumors. Among the many liquid biopsy biomarkers, miRNA is widely distributed and has been found in tissues, blood, urine and other body fluids. Therefore, the detection of circulating miRNA is an effective strategy for cancer diagnosis, prognosis and monitoring based on liquid biopsy.

[0003] In existing research, gold nanoparticles are deeply loved by researchers due to their excellent performance. However, the gold nanoparticles prepared by traditional methods are easy to agglomerate and difficult to preserve for a long time. At the same time, the yield is low, it cannot be used in high concentration, and the post-modification method is single.

[0004] Therefore, it is urgent to develop a preparation method to improve the size, morphology and stability of gold nanoparticles, which will help further promote the efficient detection of miRNAs.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a hybrid gold nanoparticle and a preparation method and application thereof. The hybrid gold nanoparticle of the present invention is a water-soluble gold nanoparticle with controllable size, uniform morphology and good stability, and can be used as a detection reagent for miRNA.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0008] In a first aspect, the present invention provides a hybrid gold nanoparticle, wherein the hybrid gold nanoparticle comprises a star-shaped polymer template and gold nanoparticles loaded on the star-shaped polymer template;

[0009] The star-shaped polymer template has a structure as shown in the following formula I:

[0010]

[0011] Wherein, PAMAM represents a dendritic macromolecule polyamidoamine, n is 20 to 100, m is 30 to 400, and the X group represents a protective group of a carboxyl group or an amino group.

[0012] Preferably, the particle size of the hybrid gold nanoparticles is 20 to 40 nm.

[0013] Preferably, the protecting group of the amino group is selected from any one of Fmoc, Dmb or Bn, preferably Fmoc.

[0014] In a second aspect, the present invention provides a method for preparing the hybrid gold nanoparticles as described in the first aspect, the preparation method comprising the following steps:

[0015] (1) 5-benzyl glutamic acid ester N-carboxyl cyclic anhydride is polymerized with dendritic macromolecule polyamide-amine to obtain a polymer PAMAM-PBLG-NH2;

[0016] (2) using a bromination reagent to perform a first modification on the terminal amino group of the polymer PAMAM-PBLG-NH2 to obtain a polymer PAMAM-PBLG-Br; and then using an azide reagent to perform a second modification on the terminal group of the polymer PAMAM-PBLG-Br to obtain a polymer PAMAM-PBLG-N3;

[0017] (3) The polymer PAMAM-PBLG-N3 undergoes a click reaction with terminal functionalized alkynyl polyethylene glycol to obtain the polymer PAMAM-PBLG-PEG;

[0018] (4) Under the combined action of trifluoroacetic acid and hydrobromic acid, the polymer PAMAM-PBLG-PEG reacts to obtain a star-shaped polymer template as shown in Formula I;

[0019] (5) The star-shaped polymer template shown in Formula I is complexed with chloroauric acid and reduced under the action of a reducing agent to obtain the hybrid gold nanoparticles.

[0020] Preferably, in step (1), the branching degree of the PAMAM is in the range of 16 to 256 (G2-G6).

[0021] Preferably, in step (1), the molecular weight of the polymer PAMAM-PBLG-NH2 ranges from 80,000 to 5,120,000 Dalton.

[0022] Preferably, in step (1), the molar ratio of the 5-benzyl glutamate N-carboxyl cyclic anhydride to the dendritic macromolecular polyamide-amine is (20-100):1.

[0023] Preferably, in step (1), the polymerization reaction temperature is 10 to 40° C., and the polymerization reaction time is 6 to 10 hours.

[0024] Preferably, in step (1), the polymerization reaction is carried out in a solvent, and the solvent includes dichloromethane.

[0025] Preferably, in step (1), after the polymerization reaction is completed, the following post-treatment step is further included: the reaction solution obtained by the polymerization reaction is concentrated, and then precipitated with diethyl ether to obtain the polymer PAMAM-PBLG-NH2.

[0026] Preferably, in step (2), the bromination reagent is 2-bromoisobutyryl bromide.

[0027] Preferably, in step (2), the molar ratio of the bromination reagent to the terminal amino group of the polymer PAMAM-PBLG-NH2 is (1-3):1.

[0028] Preferably, in step (2), during the first modification, the reaction is first carried out at -5 to 5°C for 1 to 3 hours, and then at 10 to 40°C for 20 to 24 hours.

[0029] Preferably, in step (2), during the first modification, the modification is carried out in the presence of a solvent, and the solvent comprises DMF.

[0030] Preferably, in step (2), after the first modification is completed, the following post-treatment step is further included: the reaction solution obtained by the first modification is precipitated with ether and water in sequence to obtain the polymer PAMAM-PBLG-Br.

[0031] Preferably, in step (2), the azide reagent is sodium azide.

[0032] Preferably, in step (2), the molar ratio of the azide reagent to the terminal bromine group of the polymer PAMAM-PBLG-Br is (18-22):1.

[0033] Preferably, in step (2), during the second modification, the modification temperature is 10 to 40° C., and the modification time is 22 to 26 hours.

[0034] Preferably, in step (2), the second modification is carried out in the presence of a solvent, and the solvent includes DMF.

[0035] Preferably, in step (2), after the second modification is completed, the following post-treatment step is further included: dissolving the reaction solution obtained by the second modification with dichloromethane, washing with water to remove the unreacted azide reagent, concentrating the organic phase, and then using ether for precipitation to obtain the polymer PAMAM-PBLG-N3.

[0036] Preferably, in step (3), the molecular weight of the terminal functionalized alkynyl polyethylene glycol is 2000 to 20000 Dalton.

[0037] Preferably, in step (3), the click reaction is carried out in the presence of a catalyst; wherein the catalyst is ascorbic acid.

[0038] Preferably, in step (3), the click reaction is carried out in the presence of a promoter; wherein the promoter is copper sulfate.

[0039] Preferably, in step (3), the click reaction is carried out in the presence of a ligand; wherein the ligand is pentamethyldiethylenetriamine.

[0040] Preferably, in step (3), the molar ratio of the terminal functionalized alkynyl polyethylene glycol, polymer PAMAM-PBLG-N3, catalyst, promoter and ligand is (1-2):(0.5-1.5):(0.5-1.5):(0.5-1.5):(0.5-1.5).

[0041] Preferably, in step (3), the temperature of the click reaction is 30 to 50° C., and the time of the click reaction is 22 to 26 hours.

[0042] Preferably, in step (3), the click reaction is carried out in the presence of a solvent, and the solvent includes DMF.

[0043] Preferably, in step (3), after the click reaction is completed, the following post-treatment step is further included: dialyzing and freeze-drying the reaction solution obtained by the click reaction to obtain the polymer PAMAM-PBLG-PEG.

[0044] Preferably, in step (3), the molecular weight of the dialyzed solution is 500 to 10,000 Dalton.

[0045] Preferably, in step (3), the dialysis time is 48 to 96 hours.

[0046] Preferably, in step (4), the volume ratio of trifluoroacetic acid to hydrobromic acid is (2-4):1.

[0047] Preferably, in step (4), the concentration of trifluoroacetic acid is 90 to 150 mg / mL.

[0048] Preferably, in step (4), the concentration of the hydrobromic acid is 30 to 50 mg / mL.

[0049] Preferably, in step (4), the reaction temperature is 10 to 40° C., and the reaction time is 2 to 6 hours.

[0050] Preferably, in step (4), after the reaction is completed, the following post-treatment step is further included: dialyzing and freeze-drying the reaction solution obtained by the reaction to obtain the star polymer template represented by formula I.

[0051] Preferably, in step (4), the molecular weight of the dialyzed solution is 500 to 10,000 Dalton.

[0052] Preferably, in step (4), the dialysis time is 48 to 96 hours.

[0053] Preferably, in step (5), the reducing agent is borane tert-butylamine complex.

[0054] Preferably, in step (5), the molar ratio of the chloroauric acid, the reducing agent and the carboxyl group in the star polymer template represented by formula I is (4-6):(8-12):1.

[0055] Preferably, in step (5), the complexing temperature is 10 to 40° C., and the complexing time is 42 to 54 hours.

[0056] Preferably, in step (5), the reduction temperature is 50 to 70° C., and the reduction time is 1 to 3 hours.

[0057] In a third aspect, the present invention provides a use of the hybrid gold nanoparticles as described in the first aspect as a detection agent for miRNA.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] (1) The preparation method of the present invention uses the star-shaped polymer template shown in Formula I to complex with the precursor chloroauric acid, and obtains water-soluble gold nanoparticles with controllable size, uniform morphology and good stability under the action of a reducing agent.

[0060] (2) The steps for preparing the star-shaped polymer template represented by Formula I described in the present invention are simple, highly repeatable, and can be mass-produced, providing a useful reference for the preparation of various inorganic nanoparticles that are difficult to synthesize.

[0061] (3) The hybrid gold nanoparticles of the present invention can be used in the detection of miRNA. They are coupled with double-stranded DNA. When the target miRNA appears, one of the DNA strands in the double strand will be replaced, and the reporter strand with the FAM group will be released, and the fluorescent signal will be detected. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0063] Figure 1 This is the SEC characterization chart of the molecular weight of the polymer PAMAM-PBLG-NH2 provided in Example 1.

[0064] Figure 2 This is the infrared characterization diagram of the polymer PAMAM-PBLG-N3 provided in Example 1.

[0065] Figure 3 This is the NMR characterization chart of the polymer PAMAM-PBLG-PEG provided in Example 1.

[0066] Figure 4 This is a TEM characterization image of the hybrid gold nanoparticles provided in Example 1.

[0067] Figure 5 This is a fluorescence image of the hybrid gold nanoparticles provided in Example 1 detecting miRNA. DETAILED DESCRIPTION

[0068] Unless otherwise defined herein, scientific and technological terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0069] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0070] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0071] In a first aspect, the present invention provides a hybrid gold nanoparticle, wherein the hybrid gold nanoparticle comprises a star-shaped polymer template and gold nanoparticles loaded on the star-shaped polymer template;

[0072] The star-shaped polymer template has a structure as shown in the following formula I:

[0073]

[0074] Wherein, PAMAM represents a dendritic macromolecule polyamidoamine, n is 20 to 100, m is 30 to 400, and the X group represents a protective group of a carboxyl group or an amino group.

[0075] In the present invention, the star polymer template shown in Formula I (PAMAM-PLG-PEG for short) is used to complex with the precursor chloroauric acid, and under the action of a reducing agent, water-soluble gold nanoparticles with controllable size, uniform morphology and good stability can be obtained. The PAMAM-PLG-PEG provided by the present invention can effectively solve the problems that gold nanoparticles are easy to agglomerate during the preparation process, have poor stability, are difficult to store for a long time, have low yield, cannot be used in high concentration, and have a single post-modification method.

[0076] As an optional embodiment, n is 20-100, for example, it can be 20 / 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, etc.

[0077] As an optional embodiment, m is 30-400, for example, 30, 40, 50, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, 220, 240, 260, 280, 300, 320, 340, 360, 380, 400, etc. As an optional embodiment, the particle size of the hybrid gold nanoparticles is 20-40 nm, for example, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, 32 nm, 34 nm, 36 nm, 38 nm, 40 nm, etc.

[0078] As an optional embodiment, the amino protecting group is selected from any one of Fmoc, Dmb or Bn, preferably Fmoc.

[0079] In a second aspect, the present invention provides a method for preparing the hybrid gold nanoparticles as described in the first aspect, the preparation method comprising the following steps:

[0080] (1) 5-benzyl glutamic acid ester N-carboxyl ring anhydride is polymerized with dendritic macromolecule polyamide-amine to obtain polymer PAMAM-PBLG-NH2; the reaction formula is as follows:

[0081]

[0082] (2) using a bromination reagent to perform a first modification on the terminal amino group of the polymer PAMAM-PBLG-NH2 to obtain a polymer PAMAM-PBLG-Br; then using an azide reagent to perform a second modification on the terminal group of the polymer PAMAM-PBLG-Br to obtain a polymer PAMAM-PBLG-N3; the reaction formula is as follows: The reaction formula is as follows:

[0083]

[0084] (3) The polymer PAMAM-PBLG-N3 undergoes a click reaction with the terminal functionalized alkynyl polyethylene glycol to obtain the polymer PAMAM-PBLG-PEG; the reaction formula is shown below:

[0085]

[0086] (4) Under the combined action of trifluoroacetic acid and hydrobromic acid, the polymer PAMAM-PBLG-PEG reacts to obtain a star-shaped polymer template as shown in Formula I; the reaction formula is as follows:

[0087]

[0088] (5) The star-shaped polymer template shown in Formula I is complexed with chloroauric acid and reduced under the action of a reducing agent to obtain the hybrid gold nanoparticles.

[0089] In the present invention, dendritic macromolecule polyamide-amine (PAMAM) with different branching degrees is used as an initiator to initiate the polymerization reaction of 5-benzyl glutamic acid N-carboxyl ring anhydride (BLG-NCA), and the end group is modified and the end group functionalized alkynyl polyethylene glycol (ALK-PEG-X) is grafted by click reaction, and finally deprotected under the joint action of trifluoroacetic acid and hydrobromic acid to obtain a water-soluble star polymer template (PAMAM-PLG-PEG). Then, the precursor chloroauric acid is added to make it complex with the PLG segment in PAMAM-PLG-PEG, and water-soluble gold nanoparticles with controllable size, uniform morphology and good stability are obtained under the action of a reducing agent, and are applied in the detection of miRNA. The polymer template prepared by the present invention has simple steps, strong repeatability and can be mass-produced, providing a useful reference for the preparation of various inorganic nanoparticles that are difficult to synthesize.

[0090] As an optional embodiment, in step (1), the branching degree of the PAMAM is in the range of 16 to 256 (G2-G6).

[0091] As an optional embodiment, in step (1), the molecular weight range of the polymer PAMAM-PBLG-NH2 is 80000 to 5120000 Dalton, for example, it can be 80000 Dalton, 100000 Dalton, 150000 Dalton, 200000 Dalton, 250000 Dalton, 300000 Dalton, 350000 Dalton, 400000 Dalton, 450000 Dalton, 500000 Dalton, 600000 Dalton, 800000 Dalton, 1000000 Dalton, 2000000 Dalton, 3000000 Dalton, 4000000 Dalton, 5000000 Dalton, 5120000 Dalton, etc.

[0092] As an optional embodiment, in step (1), the molar ratio of the 5-benzyl glutamate N-carboxyl ring anhydride to the dendritic macromolecular polyamide-amine is (20-100):1, for example, it can be 20:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, etc.

[0093] As an optional embodiment, in step (1), the polymerization reaction temperature is 10-40°C, for example, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc., and the polymerization reaction time is 6-10h, for example, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, etc.

[0094] As an optional embodiment, in step (1), the polymerization reaction is carried out in a solvent, and the solvent includes dichloromethane.

[0095] As an optional embodiment, in step (1), after the polymerization reaction is completed, the following post-treatment step is further included: the reaction solution obtained from the polymerization reaction is concentrated, and then precipitated with ether to obtain a polymer PAMAM-PBLG-NH2.

[0096] As an optional embodiment, in step (2), the bromination reagent is 2-bromoisobutyryl bromide.

[0097] As an optional embodiment, in step (2), the molar ratio of the bromination reagent to the terminal amino group of the polymer PAMAM-PBLG-NH2 is (1-3):1, for example, it can be 1:1, 1.2:1, 1.4:1, 1.5:1, 1.6:1, 1.8:1, 2:1, 2.2:1, 2.4:1, 2.5:1, 2.6:1, 2.8:1, 3:1, etc.

[0098] As an optional embodiment, in step (2), during the first modification, the reaction is first carried out at -5 to 5°C (for example, -5°C, -4°C, -3°C, -2°C, -1°C, 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, etc.) for 1 to 3 h (for example, 1 h, 1.2 h, 1.4 h, 1.5 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.5 h, 2.6 h, 2.8 h, 3 h, etc.), and then at 10 to 40°C (for example, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc.) for 20 to 24 h (for example, 20 h, 20.5 h, 21 h, 21.5 h, 22 h, 22.5 h, 23 h, 23.5 h, 24 h, etc.).

[0099] As an optional embodiment, in step (2), during the first modification, the modification is carried out in the presence of a solvent, and the solvent includes DMF.

[0100] As an optional embodiment, in step (2), after the first modification is completed, the following post-treatment step is further included: the reaction solution obtained by the first modification is precipitated with ether and water in sequence to obtain a polymer PAMAM-PBLG-Br.

[0101] As an optional embodiment, in step (2), the azide reagent is sodium azide.

[0102] As an optional embodiment, in step (2), the molar ratio of the azide reagent to the terminal bromine group of the polymer PAMAM-PBLG-Br is (18-22):1, for example, it can be 18:1, 18.5:1, 19:1, 19.5:1, 20:1, 20.5:1, 21:1, 21.5:1, 22:1, etc.

[0103] As an optional embodiment, in step (2), during the second modification, the modification temperature is 10-40°C, for example, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc., and the modification time is 22-26h, for example, 22h, 22.5h, 23h, 23.5h, 24h, 24.5h, 25h, 25.5h, 26h, etc.

[0104] As an optional embodiment, in step (2), the second modification is carried out in the presence of a solvent, and the solvent includes DMF.

[0105] As an optional embodiment, in step (2), after the second modification is completed, the following post-treatment step is also included: dissolving the reaction solution obtained by the second modification with dichloromethane, washing with water to remove the unreacted azide reagent, concentrating the organic phase, and then using ether for precipitation to obtain the polymer PAMAM-PBLG-N3.

[0106] As an optional embodiment, in step (3), the molecular weight of the terminal functionalized alkynyl polyethylene glycol is 2000-20000 Dalton, for example, it can be 2000 Dalton, 3000 Dalton, 4000 Dalton, 5000 Dalton, 6000 Dalton, 7000 Dalton, 8000 Dalton, 9000 Dalton, 10000 Dalton, 11000 Dalton, 12000 Dalton, 13000 Dalton, 14000 Dalton, 15000 Dalton, 16000 Dalton, 17000 Dalton, 18000 Dalton, 19000 Dalton, 20000 Dalton, etc.

[0107] As an optional embodiment, in step (3), the click reaction is carried out in the presence of a catalyst; wherein the catalyst is ascorbic acid.

[0108] As an optional embodiment, in step (3), the click reaction is carried out in the presence of a promoter; wherein the promoter is copper sulfate.

[0109] As an optional embodiment, in step (3), the click reaction is carried out in the presence of a ligand; wherein the ligand is pentamethyldiethylenetriamine.

[0110] As an optional embodiment, in step (3), the molar ratio of the end-functionalized alkynyl polyethylene glycol, polymer PAMAM-PBLG-N3, catalyst, promoter and ligand is (1-2):(0.5-1.5):(0.5-1.5):(0.5-1.5):(0.5-1.5), for example, it can be 1:1:1:1:1, 1.1:1:1:1:1, 1.2:1:1:1:1:1, 1.3:1:1:1:1, 1.4:1:1:1:1, 1.5:1:1:1:1, etc.

[0111] As an optional embodiment, in step (3), the temperature of the click reaction is 30-50°C, for example, it can be 30°C, 32°C, 34°C, 35°C, 36°C, 38°C, 40°C, 42°C, 44°C, 45°C, 46°C, 48°C, 50°C, etc., and the time of the click reaction is 22-26h, for example, it can be 22h, 22.5h, 23h, 23.5h, 24h, 24.5h, 25h, 25.5h, 26h, etc.

[0112] As an optional embodiment, in step (3), the click reaction is carried out in the presence of a solvent, and the solvent includes DMF.

[0113] As an optional embodiment, in step (3), after the click reaction is completed, the following post-treatment step is further included: dialyzing and freeze-drying the reaction solution obtained by the click reaction to obtain the polymer PAMAM-PBLG-PEG.

[0114] As an optional embodiment, in step (3), the molecular weight of the dialysis is 500-10000 Dalton, for example, it can be 5000 Dalton, 10000 Dalton, 15000 Dalton, 20000 Dalton, 25000 Dalton, 30000 Dalton, 40000 Dalton, 50000 Dalton, 60000 Dalton, 70000 Dalton, 80000 Dalton, 90000 Dalton, 100000 Dalton, etc.

[0115] As an optional embodiment, in step (3), the dialysis time is 48 to 96 hours, for example, it can be 48 hours, 54 hours, 60 hours, 66 hours, 72 hours, 78 hours, 84 hours, 90 hours, 96 hours, etc.

[0116] As an optional embodiment, in step (4), the volume ratio of trifluoroacetic acid to hydrobromic acid is (2-4):1, for example, it can be 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1, 4:1, etc.

[0117] As an optional embodiment, in step (4), the concentration of trifluoroacetic acid is 90-150 mg / mL, for example, it can be 90 mg / mL, 95 mg / mL, 100 mg / mL, 105 mg / mL, 110 mg / mL, 115 mg / mL, 120 mg / mL, 125 mg / mL, 130 mg / mL, 135 mg / mL, 140 mg / mL, 145 mg / mL, 150 mg / mL, etc.

[0118] As an optional embodiment, in step (4), the concentration of the hydrobromic acid is 30-50 mg / mL, for example, it can be 30 mg / mL, 32 mg / mL, 34 mg / mL, 36 mg / mL, 38 mg / mL, 40 mg / mL, 42 mg / mL, 44 mg / mL, 46 mg / mL, 48 mg / mL, 50 mg / mL, etc.

[0119] As an optional embodiment, in step (4), the reaction temperature is 10-40°C, for example, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc., and the reaction time is 2-6h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, etc.

[0120] As an optional embodiment, in step (4), after the reaction is completed, the following post-treatment step is further included: dialyzing and freeze-drying the reaction solution obtained by the reaction to obtain the star polymer template shown in formula I.

[0121] As an optional embodiment, in step (4), the molecular weight of the dialysis is 500-10000 Dalton, for example, it can be 5000 Dalton, 10000 Dalton, 15000 Dalton, 20000 Dalton, 25000 Dalton, 30000 Dalton, 40000 Dalton, 50000 Dalton, 60000 Dalton, 70000 Dalton, 80000 Dalton, 90000 Dalton, 100000 Dalton, etc.

[0122] As an optional embodiment, in step (4), the dialysis time is 48 to 96 hours, for example, it can be 48 hours, 54 hours, 60 hours, 66 hours, 72 hours, 78 hours, 84 hours, 90 hours, 96 hours, etc.

[0123] As an optional embodiment, in step (5), the reducing agent is borane tert-butylamine complex.

[0124] As an optional embodiment, in step (5), the molar ratio of the chloroauric acid, the reducing agent and the carboxyl group in the star polymer template represented by formula I is (4-6):(8-12):1, for example, it can be 4:8:1, 4.2:8.5:1, 4.5:9:1, 5:10:1, 5.5:11:1, 6:12:1, etc.

[0125] As an optional embodiment, in step (5), the complexation temperature is 10-40°C, for example, it can be 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc., and the complexation time is 42-54h, for example, it can be 42h, 44h, 46h, 48h, 50h, 52h, 54h, etc.

[0126] As an optional embodiment, in step (5), the reduction temperature is 50-70°C, for example, it can be 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, etc., and the reduction time is 1-3h, for example, it can be 1h, 1.2h, 1.4h, 1.5h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.5h, 2.6h, 2.8h, 3h, etc.

[0127] In a third aspect, the present invention provides a use of the hybrid gold nanoparticles as described in the first aspect as a detection agent for miRNA.

[0128] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0129] Example 1

[0130] This embodiment provides a hybrid gold nanoparticle, which is prepared by the following steps:

[0131] S1. Preparation of polymer PAMAM-PBLG-NH2

[0132] Dendritic macromolecule polyamidoamine (PAMAM) (G2-G6) with different branching degrees was dissolved in methanol, and then quickly added to the dichloromethane solution of monomer 5-benzyl glutamic acid N-carboxyl ring anhydride (BLG-NCA), and stirred vigorously. After the reaction was completed at room temperature for 8 hours, the reaction solution was concentrated by rotation and precipitated in ether to obtain polymer PAMAM-PBLG-NH2;

[0133] The molecular weight of the polymer is characterized by Figure 1 As shown, the raw material molar molecular weight and the corresponding polymer PAMAM-PBLG-NH2 are shown as follows:

[0134] Table 1

[0135]

[0136]

[0137] S2. Preparation of PAMAM-PBLG-N3:

[0138] Dissolve the PAMAM-PBLG-NH2 with a molecular weight of 320,000 Dalton in the above Table 1 in ultra-dry DMF, and gradually add 2-bromoisobutyryl bromide (BIBB) dropwise under ice bath conditions, react at 0°C for 2 hours, and continue to react at room temperature for 22 hours. After the reaction, dilute with dichloromethane, wash with water three times, and precipitate with ether to obtain the polymer PAMAM-PBLG-Br;

[0139] The polymer PAMAM-PBLG-Br was dissolved in ultra-dry DMF, sodium azide was added, and the mixture was reacted at room temperature for 24 hours. The reaction solution was then diluted with dichloromethane, and the excess unreacted sodium azide was washed away with water. Finally, the mixture was precipitated with ether to obtain the polymer PAMAM-PBLG-N3.

[0140] The polymer PAMAM-PBLG-N3 prepared from PAMAM-PBLG-N3 with a molecular weight of 320000 Dalton in Table 1 was used as an example to carry out infrared characterization of terminal azide modification, such as Figure 2 As shown, at 2200cm -1 A characteristic peak of azide appears at

[0141] S3, polymer PAMAM-PBLG-PEG:

[0142] The product polymer PAMAM-PBLG-N3 of S2, alkynyl-polyethylene glycol-Fmoc (the molecular weight of polyethylene glycol is 5000 Dalton), anhydrous copper sulfate, and ligand PMDETA are dissolved in ultra-dry DMF, and the oxygen in the solution is removed by blowing argon for 30 minutes. Ascorbic acid dissolved in DMF is added (wherein, the molar ratio of alkynyl-polyethylene glycol-Fmoc, PAMAM-PBLG-N3, anhydrous copper sulfate, ascorbic acid, and PMDETA is 1.5:1:1:1:1), and the solution is blown again for 30 minutes to remove oxygen. The solution is reacted at 40°C for 24 hours. The reaction solution is dialyzed (the molecular weight of the dialyzed solution is 50000 Dalton, and the dialysis time is 48 hours) and freeze-dried to obtain the polymer PAMAM-PBLG-PEG.

[0143] The polymer PAMAM-PBLG-PEG was characterized by NMR. Figure 3 As shown, a is the hydrogen at the polyethylene glycol position, b is the hydrogen at the benzyl position, and c, d, and e are the hydrogen at the benzene ring position in -Fmoc, respectively.

[0144] S4. Preparation of the star polymer template (PAMAM-PLG-PEG) shown in Formula I:

[0145] The polymer PAMAM-PBLG-PEG obtained in S3 was dissolved using trifluoroacetic acid, and hydrobromic acid was added for action (wherein the volume ratio of trifluoroacetic acid (100 mg / mL) and hydrobromic acid (33 mg / mL) was 3:1; the mass of the polymer PAMAM-PBLG-PEG and the total volume ratio of the acid was 75 mg:1 mL), and the protection was removed at room temperature for 4 hours; the reaction solution was dialyzed (the molecular weight of the dialyzate was 10000 Dalton, and the dialysis time was 48 hours) and freeze-dried to obtain a water-soluble star polymer template PAMAM-PLG-PEG.

[0146] S5. Preparation of hybrid gold nanoparticles:

[0147] The polymer template PAMAM-PLG-PEG was dissolved in DMF, and the precursor chloroauric acid trihydrate was added, and the mixture was stirred at room temperature for 48 hours under a N2 atmosphere to allow the chloroauric acid to fully complex with the -COOH of the polymer PLG segment. Then, tert-butylamine borane complex TBAB (wherein the molar ratio of chloroauric acid trihydrate, TBAB, and carboxyl groups in the polymer template PAMAM-PLG-PEG was 5:10:1) was added and reacted at 60°C for 2 hours to obtain the hybrid gold nanoparticles.

[0148] Comparative Example 1

[0149] This comparative example provides a gold nanoparticle, which is prepared by the following steps:

[0150] First, 18 mg of gold chloride was mixed with 100 mL of boiling deionized water, and then 3 mL of 1% (w / v) trisodium citrate was added and stirred for 30 min. The change in the color of the solution indicated that the size of the particles had shrunk. The solution was then cooled to room temperature and finally filtered through a 0.2 mm membrane.

[0151] 50 mL of streptavidin (1 mg / mL) and 1 mL of Au NPs (pH = 6.5) were mixed and incubated at 37° C. for 30 min. Then, BSA (final concentration of 1%) was added and incubated at 37° C. for another 5 min. After centrifugation at 12500 rpm, the obtained streptavidin-modified Au NPs were redispersed in 250 mL of PBS (0.1 M, pH = 7.4) and stored at 4° C. until use.

[0152] Test Example 1

[0153] Gold nanoparticle morphology test

[0154] Test sample: hybrid gold nanoparticles provided in Example 1.

[0155] Test method: Transmission electron microscopy (TEM) characterization.

[0156] Figure 4 TEM characterization diagram of the hybrid gold nanoparticles provided in Example 1. Figure 4 As shown, the hybrid gold nanoparticles of the present invention are spherical particles of uniform size, evenly dispersed without agglomeration, and have a particle size of 20 to 40 nm.

[0157] Test Example 2

[0158] Water solubility and stability testing

[0159] Test sample: hybrid gold nanoparticles provided in Example 1.

[0160] Test method:

[0161] (1) Solubility of gold nanoparticles in water: At 25°C, stirring at 800 rpm for 10 min, the water reached saturation.

[0162] (2) Storage time of gold nanoparticles in water: Place at 25°C and humidity of 50-90% without protection from light for more than 1 year to observe whether sedimentation occurs.

[0163] Test results:

[0164] The solubility of the hybrid gold nanoparticles provided in Example 1 in water is 10 mg / mL; and the hybrid gold nanoparticles provided in Example 1 can be stored at 25°C for more than 365 days without sedimentation or deterioration. This shows that the hybrid gold nanoparticles obtained by the preparation method of the present invention not only have the advantages of controllable size and uniform morphology, but also have certain water solubility and good stability.

[0165] Test Example 3

[0166] Detection of miRNA

[0167] Test sample: hybrid gold nanoparticles provided in Example 1.

[0168] Test method: The prepared gold nanoparticles are coupled to double-stranded DNA. After the target miRNA appears, one of the DNA strands in the double strand will be replaced, and the reporter strand with the FAM group will be released to detect whether a fluorescent signal appears.

[0169] Test results:

[0170] like Figure 5 As shown, after the addition of miRNA, the fluorescence signal was restored and increased with increasing concentration.

[0171] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A hybrid gold nanoparticle, characterized in that: The hybrid gold nanoparticles include a star-shaped polymer template and gold nanoparticles loaded on the star-shaped polymer template; The star-shaped polymer template has a structure as shown in the following formula I: Wherein, PAMAM represents a dendritic macromolecule polyamidoamine, n is 20 to 100, m is 30 to 400, and the X group represents a protective group of a carboxyl group or an amino group.

2. The hybrid gold nanoparticles according to claim 1, characterized in that The particle size of the hybrid gold nanoparticles is 20-40 nm.

3. The hybrid gold nanoparticles according to claim 1, characterized in that The amino protecting group is selected from any one of Fmoc, Dmb or Bn, preferably Fmoc.

4. A method for preparing hybrid gold nanoparticles according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) 5-benzyl glutamic acid ester N-carboxyl cyclic anhydride is polymerized with dendritic macromolecule polyamide-amine to obtain polymer PAMAM-PBLG-NH2; (2) using a bromination reagent to perform a first modification on the terminal amino group of the polymer PAMAM-PBLG-NH2 to obtain a polymer PAMAM-PBLG-Br; and then using an azide reagent to perform a second modification on the terminal group of the polymer PAMAM-PBLG-Br to obtain a polymer PAMAM-PBLG-N3; (3) The polymer PAMAM-PBLG-N3 undergoes a click reaction with terminal functionalized alkynyl polyethylene glycol to obtain the polymer PAMAM-PBLG-PEG; (4) Under the combined action of trifluoroacetic acid and hydrobromic acid, the polymer PAMAM-PBLG-PEG reacts to obtain a star-shaped polymer template as shown in Formula I; (5) The star-shaped polymer template shown in Formula I is complexed with chloroauric acid and reduced under the action of a reducing agent to obtain the hybrid gold nanoparticles.

5. The method for preparing hybrid gold nanoparticles according to claim 4, characterized in that: In step (1), the branching degree of the PAMAM is in the range of 16 to 256 (G2-G6); Preferably, in step (1), the molecular weight of the polymer PAMAM-PBLG-NH2 is in the range of 80,000 to 5,120,000 Dalton; Preferably, in step (1), the molar ratio of the glutamic acid 5-benzyl ester N-carboxyl cyclic anhydride to the dendritic macromolecular polyamide-amine is (20-100):1; Preferably, in step (1), the polymerization reaction temperature is 10 to 40° C., and the polymerization reaction time is 6 to 10 hours; Preferably, in step (1), the polymerization reaction is carried out in a solvent, and the solvent comprises dichloromethane; Preferably, in step (1), after the polymerization reaction is completed, the following post-treatment step is further included: the reaction solution obtained by the polymerization reaction is concentrated, and then precipitated with diethyl ether to obtain the polymer PAMAM-PBLG-NH2.

6. The method for preparing hybrid gold nanoparticles according to claim 5, characterized in that: In step (2), the bromination reagent is 2-bromoisobutyryl bromide; Preferably, in step (2), the molar ratio of the bromination reagent to the terminal amino group of the polymer PAMAM-PBLG-NH2 is (1-3):1; Preferably, in step (2), during the first modification, the reaction is first carried out at -5 to 5°C for 1 to 3 hours, and then at 10 to 40°C for 20 to 24 hours; Preferably, in step (2), during the first modification, the modification is carried out in the presence of a solvent, and the solvent comprises DMF; Preferably, in step (2), after the first modification is completed, the following post-treatment step is further included: the reaction solution obtained by the first modification is precipitated with ether and water in sequence to obtain a polymer PAMAM-PBLG-Br; Preferably, in step (2), the azide reagent is sodium azide; Preferably, in step (2), the molar ratio of the azide reagent to the terminal bromine group of the polymer PAMAM-PBLG-Br is (18-22):1; Preferably, in step (2), during the second modification, the modification temperature is 10 to 40° C., and the modification time is 22 to 26 hours; Preferably, in step (2), during the second modification, the process is carried out in the presence of a solvent, and the solvent includes DMF; Preferably, in step (2), after the second modification is completed, the following post-treatment step is further included: dissolving the reaction solution obtained by the second modification with dichloromethane, washing with water to remove the unreacted azide reagent, concentrating the organic phase, and then using ether for precipitation to obtain the polymer PAMAM-PBLG-N3.

7. The method for preparing hybrid gold nanoparticles according to claim 5, characterized in that: In step (3), the molecular weight of the terminal functionalized alkynyl polyethylene glycol is 2000 to 20000 Dalton; Preferably, in step (3), the click reaction is carried out in the presence of a catalyst; wherein the catalyst is ascorbic acid; Preferably, in step (3), the click reaction is carried out in the presence of a promoter; wherein the promoter is copper sulfate; Preferably, in step (3), the click reaction is carried out in the presence of a ligand; wherein the ligand is pentamethyldiethylenetriamine; Preferably, in step (3), the molar ratio of the terminal functionalized alkynyl polyethylene glycol, the polymer PAMAM-PBLG-N3, the catalyst, the promoter and the ligand is (1-2):(0.5-1.5):(0.5-1.5):(0.5-1.5):(0.5-1.5); Preferably, in step (3), the temperature of the click reaction is 30 to 50° C., and the time of the click reaction is 22 to 26 hours; Preferably, in step (3), the click reaction is carried out in the presence of a solvent, and the solvent comprises DMF; Preferably, in step (3), after the click reaction is completed, the following post-treatment step is further included: dialyzing and freeze-drying the reaction solution obtained by the click reaction to obtain the polymer PAMAM-PBLG-PEG; Preferably, in step (3), the molecular weight of the dialyzed solution is 500 to 10000 Dalton; Preferably, in step (3), the dialysis time is 48 to 96 hours.

8. The method for preparing hybrid gold nanoparticles according to claim 5, characterized in that: In step (4), the volume ratio of trifluoroacetic acid to hydrobromic acid is (2-4):1; Preferably, in step (4), the concentration of trifluoroacetic acid is 90 to 150 mg / mL; Preferably, in step (4), the concentration of the hydrobromic acid is 30 to 50 mg / mL; Preferably, in step (4), the reaction temperature is 10 to 40° C., and the reaction time is 2 to 6 hours; Preferably, in step (4), after the reaction is completed, the following post-treatment step is further included: dialyzing and freeze-drying the reaction solution obtained by the reaction to obtain a star polymer template represented by formula I; Preferably, in step (4), the molecular weight of the dialyzed solution is 500 to 10,000 Dalton; Preferably, in step (4), the dialysis time is 48 to 96 hours.

9. The method for preparing hybrid gold nanoparticles according to claim 5, characterized in that: In step (5), the reducing agent is borane tert-butylamine complex; Preferably, in step (5), the molar ratio of the chloroauric acid, the reducing agent and the carboxyl group in the star polymer template represented by formula I is (4-6):(8-12):1; Preferably, in step (5), the complexing temperature is 10 to 40° C., and the complexing time is 42 to 54 hours; Preferably, in step (5), the reduction temperature is 50 to 70° C., and the reduction time is 1 to 3 hours.

10. Use of the hybrid gold nanoparticles according to claim 1 or 2 as a detection reagent for miRNA.

Citation Information

Patent Citations

  • Method for preparing PAMAM dendrimer-modified gold nanorod composite carrier

    CN101444847A

  • Targeted polyamide-amine dendrimer encapsulated nano-gold preparation method

    CN108672697A

  • Preparation method of gold nanometer particles

    CN111940755A

  • Dendrimer based nanodevices for therapeutic and imaging purposes

    US20150141350A1